EFFECT OF CURRENT RATIO, DEBT TO EQUITY RATIO AND NET PROFIT MARGIN TO PROFIT GROWTH IN AUTOMOTIVE SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2017-2021 - Dody Indrawan; Supriyanto; Tutiek Yoganingsih; Kardinah Indrianni Meutia (Draf Solusi Indonesia, 2023)
This study aims to determine the effect of Current Ratio, Debt to Equity Ratio and Net Profit Margin on profit growth in automotive sub-sector companies listed on the IDX in 2017-2021. This study uses a quantitative research approach that emphasizes theory testing by measuring research variables with numbers and analyzing data with statistical techniques. The population used is automotive sub-sector companies listed on the IDX in 2017-2021. The sampling technique was purposive sampling. The samples in this study were 14 automotive sub-sector companies that had complete data in the annual reports from 2017-2021. The data used in this study are secondary data collected through the company's annual financial statements accessed from idnfinancial and idx.co.id which are the research samples. Data collection techniques and data processing using Eviews 12. Based on the results of this study, it can be concluded that the results of the analysis test provide results that: (X1) Current Ratio partially has no effect on earnings growth, (X2) Debt to Equity Ratio partially has no effect on earnings growth, (X3) Net Profit Margin partially affects earnings growth. And (X1) Current Ratio, (X2) Debt to Equity Ratio, (X3) Net Profit Margin simultaneously affects profit growth in automotive sub-sector companies.